CARACTERÃSTICAS AGRONÃ”MICAS E PRODUTIVIDADE DE GRÃO DE CULTIVARES DE SOJA - Lemos, Leandro Borges; Farinelli, Rogério; Cavariani, Cláudio; Recco, Paulo César; Zapparoli, Rodolfo Alexandre; Cruciol, João Henrique (REVISTA DE AGRICULTURA, 2015)
CARACTERÃSTICAS AGRONÃ”MICAS E PRODUTIVIDADE DE GRÃO DE CULTIVARES DE SOJA